Case Report: Complex tricuspid valve repair and entrapped right ventricle foreign body extraction in an IVDU patient—early diagnosis and treatment considerations - Blindaru, Andreea; Copciag, Ruxandra; Anghel, Florin; Danet, Andrei; Isailă, Radu; Borjog, Tudor; Andronic, Anca; Vinereanu, Dragos; Badiu, Catalin-Constantin (Frontiers in Cardiovascular Medicine, 2025)
We report the case of a 39-year-old pregnant woman with a history of drug abuse who was admitted to the cardiology department with a diagnosis of tricuspid valve endocarditis. After the multidisciplinary team decided on a conservative treatment with antibiotherapy, the pregnancy was closely monitored. After 4 weeks of treatment, the patient developed extreme thoracic pain and pericardial effusion that was considered infectious and did not require urgent surgery. One month after giving birth to her baby, the patient was admitted to our hospital for the completion of the preoperative protocol. During this admission, multimodal imaging revealed a penetrating metallic foreign body in the wall of the right ventricle. The patient was finally admitted to the Cardiovascular Surgery Unit, where she underwent surgical removal of the foreign body and a complex tricuspid valve repair. The postoperative course was uneventful, and our patient was discharged from the ICU 2 days later.